2017
DOI: 10.1002/mp.12351
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sampling interval in training data acquisition on intrafractional predictive accuracy of indirect dynamic tumor‐tracking radiotherapy

Abstract: Purpose: To explore the effect of sampling interval of training data acquisition on the intrafractional prediction error of surrogate signal-based dynamic tumor-tracking using a gimbal-mounted linac. Materials and methods: Twenty pairs of respiratory motions were acquired from 20 patients (ten lung, five liver, and five pancreatic cancer patients) who underwent dynamic tumor-tracking with the Vero4DRT. First, respiratory motions were acquired as training data for an initial construction of the prediction model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…In a practical treatment scenario, the sampling rate of the EPID varies according to the dose rate. However, Mukumoto et al . have shown that within the sampling range of 0.08 to 0.2 s, the changes in the prediction accuracy of respiratory signals is insignificant ( P > 0.05).…”
Section: Discussionmentioning
confidence: 96%
“…In a practical treatment scenario, the sampling rate of the EPID varies according to the dose rate. However, Mukumoto et al . have shown that within the sampling range of 0.08 to 0.2 s, the changes in the prediction accuracy of respiratory signals is insignificant ( P > 0.05).…”
Section: Discussionmentioning
confidence: 96%
“…Using frequently updated input data to train a prediction model may get higher prediction accuracy. It is recommended to use the data with a sampling interval of less than 1 second to build a prediction model (33). The frame rates of the OSMS were 3-6 frame/s with a sampling time interval of 0.16-0.33 seconds, and the frame rate of the fluoroscopy in this study was 15 frames/s.…”
Section: Discussionmentioning
confidence: 92%
“…The tumor and the fiducials were monitored with OBI, in real time at a minimum interval of 0.5 s. For lung tumors, EPID can visualize the tumor positions through the delivered beams. Update or rebuild of the 4D model is performed if needed [14,15]. Finally, log files are analyzed after the treatment to evaluate tracking errors [16].…”
Section: Dynamic Tumor Trackingmentioning
confidence: 99%